2002
DOI: 10.1002/bio.671
|View full text |Cite
|
Sign up to set email alerts
|

The red‐edge effects: 30 years of exploration

Abstract: In 1970, three laboratories independently made a discovery that, for aromatic fluorophores embedded into different rigid and highly viscous media, the spectroscopic properties do not conform to classical rules. The fluorescence spectra can depend on excitation wavelength, and the excited-state energy transfer, if present, fails at the "red" excitation edge. These red-edge effects were related to the existence of excited-state distribution of fluorophores on their interaction energy with the environment and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
423
2
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 443 publications
(446 citation statements)
references
References 203 publications
20
423
2
1
Order By: Relevance
“…A similar effect was observed in the parent 3-hydroxyflavones in protic solvents where solvent hydrogen bonding with the dye may increase the activation energy barrier to ESIPT [46][47]. In this case, ESIPT is irreversible and is characterized by the fact that the average lifetime of the T* band is longer than that for the N* band [43][44]. The highest degree of ESIPT non-equilibration seems to occur in MFE doped copolymers where the difference in average lifetime (∆τ ) is ≈ 1.6 ns (Table 1), while the BFE doped copolymers have a much lower ∆τ of ≈ 0.4 ns) ( Table 3 and Figure 10A-C).…”
Section: Fluorescence Lifetime Measurementsmentioning
confidence: 55%
See 1 more Smart Citation
“…A similar effect was observed in the parent 3-hydroxyflavones in protic solvents where solvent hydrogen bonding with the dye may increase the activation energy barrier to ESIPT [46][47]. In this case, ESIPT is irreversible and is characterized by the fact that the average lifetime of the T* band is longer than that for the N* band [43][44]. The highest degree of ESIPT non-equilibration seems to occur in MFE doped copolymers where the difference in average lifetime (∆τ ) is ≈ 1.6 ns (Table 1), while the BFE doped copolymers have a much lower ∆τ of ≈ 0.4 ns) ( Table 3 and Figure 10A-C).…”
Section: Fluorescence Lifetime Measurementsmentioning
confidence: 55%
“…However, when we investigated the effect of different excitation wavelengths on the 3-HF probe loaded copolymers, we found that the intensity ratio I N* /I T* ( Figure 7A-C), and the position of the N* band ( Figure 8) varies for every dye. In solvents, this excitation dependence is not observed [32], and so it could be attributed to a classical red-edge effect which is usually observed in rigid media [42][43]. In this case, red-edge excitation will photo-select dielectrically stabilized species, which in turn leads to lower T* emission.…”
Section: -Hf Fluorescencementioning
confidence: 94%
“…It has previously been shown for 7-nitrobenz-2-oxa-1,3-diazol-4-yl (NBD)-labeled phospholipids incorporated into model membranes, that a dipole moment change of Â/4 D upon excitation is enough to give rise to significant red edge effects . A recent comprehensive review on the red edge effect is provided by Demchenko (2002).…”
Section: Red Edge Excitation Shiftmentioning
confidence: 99%
“…Discussion L-Tryptophan is a naturally occurring amino acid, with a non-polar side chain and no net charge at physiological pH. Tryptophan fluorescence is widely used as a tool to monitor changes in proteins and to make inferences regarding conformation and dynamics [3,4], The nonexponential fluorescence decay of tryptophan, in * Correspondence author (e-mail: manuela@pollux.fis.uc.pt) aqueous solutions, has been explained by the emission from noninterconverting rotamers which have different lifetimes due to different rates of intramolecular charge transfer [5]. Looking for compounds with optical properties and phase transitions, we have been synthesizing L-tiyptophan salts, namely the title compound, L-tryptophanium phosphite.…”
Section: Methodsmentioning
confidence: 99%